Identification of Critical Variables Determining the Growth of Culinary MSMEs in Banyuwangi Based on Transaction and Marketing Data Using Statistical Analysis: Identifikasi Variable Kritis Penentu Pertumbuhan UMKM Kuliner di Banyuwangi Berdasarkan Data Transaksi dan Pemasaran Menggunakan Analisis Statistik - Ratri, Arum; Indira Nuansa Ratri; I Wayan Suardinata; Eka Novita Sari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
MSMEs play a crucial role in supporting local economic growth, yet their ability to increase business performance is often constrained by limited resources and marketing strategies. This study aims to identify critical factors influencing MSME growth, measured through revenue increase, by analyzing transaction and marketing-related variables. Data were collected through questionnaires distributed to MSME owners and analyzed using Pearson correlation and multiple linear regression methods. The independent variables include transaction frequency, number of customers, promotion frequency, promotion budget, and perceived impact of social media usage. The results show that transaction frequency (r = 0.50271), number of customers (r = 0.46930), promotion frequency (r = 0.40632), and perceived impact of social media (r = 0.56519) have a moderate positive correlation with revenue growth, while promotion budget (r = -0.00196) has no significant correlation. Multiple regression analysis indicates that the model explains 51.67% of revenue growth variation (R² = 0.5167). Partially, transaction frequency, promotion frequency, and perceived social media impact significantly affect revenue growth, whereas customer number and promotion budget do not.